“Factors in the development of speaking skills in efl” - Maji Lema, Jorge Samuel (2023)
The English language has acquired great importance in the educational system around the world. One of the most important skills is speaking. But it has been evidenced that some students tend to present problems in the development of English speaking in the classroom. This may be associated with different factors in the teaching of English as a foreign language. The present study aims to determine the factors that affect the development of oral proficiency in high school students of Delia Ibarra de Velasco High School during the 2022-2023 school year. The present study was developed with a mixed method (quantitative-qualitative). Therefore, being a mixed approach research, a semi-structured interview guide was used with English teachers to learn their opinions about the most important factors that hinder the development of oral proficiency and how this problem could be alleviated. In addition, the researcher applied a questionnaire to determine what factors affect the development of oral skills from the students' point of view. The population for this research consisted of 50 students from the Delia Ibarra de Velasco Educational Unit in the province of Cotopaxi, Canton Pujilí; 22 males and 28 females between 14 and 18 years of age. The results of the semi-structured interview show that cultural boundaries and the use of the mother tongue are factors that significantly affect the students. The students consider that English is not as important as their mother tongue, which is Kichwa. On the other hand, the results of the questionnaire that was applied to identify the factors that affect the development of speaking skills showed that affective factors, the role of the teacher and the educational environment in relation to the learning of speaking skills moderately affect the development of the students' speaking skills. It is important to prioritize affective factors, teacher role and educational environment in EFL development and to adapt planning, methods and teaching strategies according to students' needs.